Internet - Based Security and Monitoring System - Suliman, Isameldin Mohammed (1998)
This study describes a remote monitoring and security system based on the Internt. It is intended to investigate the possibilities of using the integration of the Internet and telephone lines in providing solution to security problems by conveying alarm signals from remote monitored locations. developed to allow selected users to get monitoring and security information. A special purpose web server was designed to handle the system. This web server which is acting as a central monitoring station will supply the system's users with information reporting any intrusion at remote monitored locations The system utilised the existing telephone network , and user friendly in alarm transmission from remote monitored location. modem was used to maintain interface between the telephone line and the web server. data capturing from the modem through the serial port web server . Java language was used for developing a server program that is running in the back ground to enable data provided by the communication program to be put on the Internet for access. A graphical user interface (Java applets) implemented to allow users to access the system. The results of applying this approach showed the possibilities of using the integration of the Internet and telephone lines in conveying alarm signals and control command. It also emphasised the import developing software programs for Internet-based systems . Furthermore, is still required to fill the low-level interface gap that was not supported by Java language. Finally, Internet can be used not only for information exchange and retrieval, as a communication medium for monitoring and controlling of remote physical environments.